2017
DOI: 10.3892/or.2017.5838
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of miR-138 in patients with malignant melanoma through targeting of PDK1 in the PI3K/AKT autophagy signaling pathway

Abstract: The present study investigated the clinical significance of miR-138 in patients with malignant melanoma (MM), which has previously been associated with tumor growth. In patients with MM, we found that the expression of miR-138 was significantly downregulated when compared with healthy control subjects. Overexpression of miR-138 in the human melanoma cell line A2058 inhibited cell proliferation and induced cell apoptosis, and increased caspase-3 and Bax protein expression when compared with a negative control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Jiang and Liu reported that miR-25 target the RNA-binding motif protein 47 (RBM47) and activated the PI3K/Akt/mTOR signaling pathway in melanoma cells [116]. Meng et al recently demonstrated clinically that miR-138 is significantly upregulated in malignant melanoma patients by regulating the PI3K/Akt/mTOR autophagy pathway via PDK1 dependent expression [117]. Moreover, a study by Li et al also reported that by targeting PIK3R3/AKT3, miR-224-5p suppressed proliferation, migration, and invasion in uveal melanoma (UM) cells, representing a therapeutic and diagnosis target for patients with UM [115].…”
Section: Cutaneous Cancers Associated With Dysregulation Of the Pimentioning
confidence: 99%
“…Jiang and Liu reported that miR-25 target the RNA-binding motif protein 47 (RBM47) and activated the PI3K/Akt/mTOR signaling pathway in melanoma cells [116]. Meng et al recently demonstrated clinically that miR-138 is significantly upregulated in malignant melanoma patients by regulating the PI3K/Akt/mTOR autophagy pathway via PDK1 dependent expression [117]. Moreover, a study by Li et al also reported that by targeting PIK3R3/AKT3, miR-224-5p suppressed proliferation, migration, and invasion in uveal melanoma (UM) cells, representing a therapeutic and diagnosis target for patients with UM [115].…”
Section: Cutaneous Cancers Associated With Dysregulation Of the Pimentioning
confidence: 99%
“…Our study revealed several miRNAs that were associated with ESRP1, including miRNA-138. Researchers have found that miR-138, miR-155, and miR-221/222 can be used as the diagnostic and prognostic markers of CMM [ 36 – 38 ]. Some studies have reported that miR-138 has tumor-suppressive effects in malignant diseases of the lung, kidney, tongue, head, and neck [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are a number of studies about micro-RNAs and CM [25][26][27][28] but fewer about lncRNAs and CM. LncRNAs ANRIL [29], BANCR [30], GAS5 [31,32], MALAT1 [33], PVT1 [34,35], SAMMON [36,37], SPRIGHTLY [38,39], SPRY4-1T1 [40,41], and other lncRNAs have been studied for the regulation of melanocyte proliferation, migration, invasion, and other cell biological functions associated with the development and metastasis of CM.…”
Section: Discussionmentioning
confidence: 99%